Strategi Pemasaran Pelayanan Continuous Ambulatory Peritoneal Dialysis di Klinik Khusus Ginjal X Batam Tahun 2016 - Toha, Bertha; Permanasari, Vetty Y ulianty (Jurnal Ekonomi Kesehatan Indonesia, 2017)
Currently only 53% of patients with end-stage renal disease that can access dialysis and mostly get Hemodialysis (HD), whereas the cost to Continous Ambulatory Peritoneal Dialysis (CAPD) cheaper than HD (Ministry of Health, 2016). Services of CAPD in Clinic for Kidney Disease X. Batam began since 2010, but the number of CAPD patients only 3% of the end stage renal disease patients there. The purpose of this study to analyze the Marketing Strategy of Continuous Ambulatory Peritoneal Dialysis Services at the Clinic for Kidney Disease X Batam Year 2016. The design of the study is an analytic descriptive with quantitative and qualitative approaches. Stages of analysis used Fred R. David strategies and followed by Segmenting, Targeting and Positioning, and then determine the marketing mix (Product, Promotion, Price, Place, People, Physical Evidence, Process, Customer Service). The Clinic has set tariffs adjusted rates INA-CBG’s package but has not calculated the cost of the unit. A Marketing strategy that good and proper with the analysis of the situation are: Market Penetration and Product Development. Product marketing services in Clinic for Kidney Disease X Batam can be advertised through various media such as radio talk shows, Local Batam station of television talk shows and leaflets; distribute leaflets in the service room of Medicine; sales promotion, and training for doctors in health primary care. In addition, promotion of CAPD can use online or social media. In order to avoid asimetric information, the doctors have responsible for giving a comprehensive education on CAPD therapy.